Cardiovascular function and ozone exposure: The Multicenter Ozone Study in oldEr Subjects (MOSES). (October 2018) - Rich, David Q.; Balmes, John R.; Frampton, Mark W.; Zareba, Wojciech; Stark, Paul; Arjomandi, Mehrdad; Hazucha, Milan J.; Costantini, Maria G.; Ganz, Peter; Hollenbeck-Pringle, Danielle; Dagincourt, Nicholas; Bromberg, Philip A.
Abstract: Background: To date, there have been relatively few studies of acute cardiovascular responses to controlled ozone inhalation, although a number of observational studies have reported significant positive associations between both ambient ozone levels and acute cardiovascular events and long-term ozone exposure and cardiovascular mortality. Objectives: We hypothesized that short-term controlled exposure to low levels of ozone in filtered air would induce autonomic imbalance, repolarization abnormalities, arrhythmia, and vascular dysfunction. Methods: This randomized crossover study of 87 healthy volunteers 55–70 years of age was conducted at three sites using a common protocol, from June 2012 to April 2015. Subjects were exposed for 3 h in random order to 0 ppb (filtered air), 70 ppb ozone, and 120 ppb ozone, alternating 15 min of moderate exercise with 15 min of rest. A suite of cardiovascular endpoints was measured the day before, the day of, and up to 22 h after each exposure. Mixed effect linear and logit models evaluated the impact of exposure to ozone on pre-specified primary and secondary outcomes. Site and time were included in the models. Results: We found no significant effects of ozone exposure on any of the primary or secondary measures of autonomic function, repolarization, ST segment change, arrhythmia, or vascular function (systolic blood pressure and flow-mediated dilation). Conclusions: In this multicenter study of older healthy women and men, there was no convincing evidence for acute effects of 3-h, relatively low-level ozone exposures on cardiovascular function. However, we cannot exclude the possibility of effects with higher ozone concentrations, more prolonged exposure, or in subjects with underlying cardiovascular disease. Further, we cannot exclude the possibility that exposure to ambient ozone and other pollutants in the days before the experimental exposures obscured or blunted cardiovascular biomarker response to the controlled ozone exposures. Highlights: Randomized crossover study of 87 healthy volunteers 55-70 years of age. Exposures of 3 h in random order to 0, 70, and 120 ppb ozone, alternating 15 min of moderate exercise with 15 min of rest. No ozone effects on measures of autonomic function, repolarization, ST segment change, arrhythmia, or vascular function.